People's Republic of China-Hong Kong Special Administrative Region : 2017 Article IV Consultation-Press Release; Staff Report; Statement by the Executive Director for People's Republic of China--Hong Kong Special Administrative Region. (IMF Staff Country Reports; Country Report ;, 2018)
This 2017 Article IV Consultation highlights that economic activity in Hong Kong Special Administrative Region has gained momentum since the second half of 2016 amid robust domestic demand and recovering external demand. Growth is projected to have risen by 3.7 percent in 2017, up from 2 percent in 2016. The strong growth momentum is expected to continue in the near term with annual growth of 2.8 percent in 2018. Consumption is projected to continue to be supported by a tight labor market and investment is expected to remain strong, with major infrastructure and housing projects in the pipeline. The economy is expected to continue to grow at about 3 percent over the medium term, close to its potential.